Wetting and interfacial behavior of Fe-based self-fluxing alloy–refractory compound systems - Umanskyi, O. P.; Pareiko, M. V.; Storozhenko, M. S.; Krasovskyy, V. P. (Journal of superhard materials, 2017)
In this study the wettability and interfacial behaviour of the TiC–FeNiCrBSiC and TiB 2 –FeNiCrBSiC systems were investigated. The wetting experiments were performed by the sessile drop method at 1150°C under a vacuum. The contact angles of TiC and TiB 2 wetting by melted Fe-based self-fluxing alloy were 51° and 36°, respectively. Thermodynamic calculations were carried out to understand the metal–ceramic interaction mechanism in the TiC–FeNiCrBSiC and TiB 2 –FeNiCrBSiC systems. The structure of the interface region in the TiB 2 –FeNiCrBSiC system was characterized by the optical microscopy and SEM-EDS analysis. The formation of Fe, Ni, Cr and Mo complex borides was revealed within the interface region of the TiB 2 –FeNiCrBSiC system.